Why we should all care about social institutions related to gender inequality - Boris Branisa; Stephan Klasen; Maria Ziegler (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
Institutions are a major factor explaining development outcomes. This study focuses on social institutions related to gender inequality understood as long-lasting norms, values and codes of conduct that shape gender roles, and presents evidence on why they matter for development. We derive hypotheses from existing theories and empirically test them at the cross-country level with linear regressions using the newly created Social Institutions and Gender Index (SIGI) and its subindices as measures for social institutions. We find that apart from geography, political system, religion, and the level of economic development, one has to consider social institutions related to gender inequality to better account for differences in development. Our results show that social institutions that deprive women of their autonomy and bargaining power in the household, or that increase the private costs and reduce the private returns to investments into girls, are associated with lower female education, higher fertility rates and higher child mortality. Moreover, social institutions related to gender inequality are negatively associated with governance measured as rule of law and voice and accountability.
Keywords: D63; I10; I20; H1; J16; 330; Social institutions; SIGI; Gender inequality; Fertility; Child mortality; Female education; Governance